Representasi Spiritualitas dan Krisis Diri Manusia Modern: Telaah Pemikiran Seyyed Hossein Nasr dalam Budaya Media Sosial - Nisa Syahrani (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
The development of social media has shifted the way humans interpret spirituality and construct self-identity, giving rise to the phenomenon of digital religiosity that is all-visual, instant, and performative. This study aims to analyze how representations of spirituality in social media culture contribute to the crisis of self in modern humans, by interpreting this phenomenon through the metaphysical perspective of Seyyed Hossein Nasr. Using a qualitative approach with a descriptive-analytical design that enriches digital ethnography, this study collects data through documentation of spirituality-themed content on TikTok, Instagram, and YouTube, as well as a literature review of Nasr's works and literature related to digital spirituality. Thematic analysis shows that spirituality in social media is formed through symbolic aestheticization, the commodification of religious values, and identity performances oriented towards algorithms and public validation. These findings demonstrate the symptoms of the desacralization of modernity as criticized by Nasr, namely the erosion of spiritual depth due to the dominance of images and the narrowing of transcendent meaning. This study emphasizes that social media is not just a medium, but a space for the formation of consciousness that can facilitate and endeavor the spiritual search of modern humans. Theoretically, this research contributes to the study of digital spirituality and the critique of modernity; In practice, he encourages more critical digital literacy so that people can manage spiritual experiences more authentically.